The role of non-profit organizations : an economic analysis - Vajčner, David; Klosová, Anna, 1942-; Jackson, Ian; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
This thesis investigates the economic theories on the role on non-profit organizations, their creation, and factors for the size of the non-profit sector. An analytical approach was taken to determine what factors seem to affect the size of the non-profit sector. Firstly a literature review was conducted of the existing, and predominant economic theories relating to the role of the non-profit sector, and several hypotheses where suggested from the analysis of past research. Then an empirical model was created to test the validity of the hypotheses on a cross-national sample, in an effort to deduce what factors affect the size of the non-profit sector.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses